Learning difficulties for out-of-home care pre-teens and teenagers: school implications, research challenges and new educational directions - Ricchiardi, Paola (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2022)
Studies on Adverse Childhood Experiences (ACEs) have increased in different countries, to identify their short- and long-term effects on minor life trajectories. Particular attention was paid to the negative effects of ACEs on school integration and learning. International research has consistently attested and with convergence, in various countries, the presence of learning difficulties among minors who spent a period of time in contest with numerous risk factors, prior to placement. Studying our context, especially with attention to identifying protective factors, is important to prevent the difficulties of children in OOHC. In this contribution, we present a survey in the Municipality of Turin in the years 2021/22 with a sample of 111 minors (from 10 to 17 years), partly in foster care and partly in residential service, aimed not only to describe the phenomenon, but also to detect specific areas for improvement of the care system. In fact, the research also investigates the support strategies used by educators to cope with these difficulties. The results of the survey have significant educational implications, for the work and for the training of professionals involved in the care and support process, in particular for educators. New challenges also emerge for pedagogical research on the subject, more frequently approached from other perspectives (sociological, psychological, legal).